Iron overload contributes to general anaesthesia-induced neurotoxicity and cognitive deficits - Wu, Jing; Yang, Jian-Jun; Cao, Yan; Li, Huihui; Zhao, Hongting; Yang, Shuofei; Li, Kuanyu (Journal of neuroinflammation, 2020)
Background Increasing evidence suggests that multiple or long-time exposure to general anaesthesia (GA) could be detrimental to cognitive development in young subjects and might also contribute to accelerated neurodegeneration in the elderly. Iron is essential for normal neuronal function, and excess iron in the brain is implicated in several neurodegenerative diseases. However, the role of iron in GA-induced neurotoxicity and cognitive deficits remains elusive. Methods We used the primary hippocampal neurons and rodents including young rats and aged mice to examine whether GA impacted iron metabolism and whether the impact contributed to neuronal outcomes. In addition, a pharmacological suppression of iron metabolism was performed to explore the molecular mechanism underlying GA-mediated iron overload in the brain. Results Our results demonstrated that GA, induced by intravenous ketamine or inhalational sevoflurane, disturbed iron homeostasis and caused iron overload in both in vitro hippocampal neuron culture and in vivo hippocampus. Interestingly, ketamine- or sevoflurane-induced cognitive deficits, very likely, resulted from a novel iron-dependent regulated cell death, ferroptosis. Notably, iron chelator deferiprone attenuated the GA-induced mitochondrial dysfunction, ferroptosis, and further cognitive deficits. Moreover, we found that GA-induced iron overload was activated by NMDAR-RASD1 signalling via DMT1 action in the brain. Conclusion We conclude that disturbed iron metabolism may be involved in the pathogenesis of GA-induced neurotoxicity and cognitive deficits. Our study provides new vision for consideration in GA-associated neurological disorders.